Peningkatan Hasil Belajar Siswa melalui Metode Diskusi Kelompok pada Mata Pelajaran PAI-BP di Kelas X SMKN 5 Padang - Isral Isral (Jurnal Pendidikan Tuntas, 2024)
This Classroom Action Research (PTK) aims to improve student learning outcomes in the subject of Islamic Religious Education and Ethics (PAI-BP) through the application of the group discussion method in class X SMKN 5 Padang. The low student learning outcomes in the previous material indicated the need for a more active and collaborative learning strategy to increase student engagement and concept understanding. This research was conducted in two cycles, each of which consisted of planning, action, observation, and reflection stages. Data were collected through learning outcome tests, participatory observation, and student response questionnaires. The results showed that the group discussion method significantly improved students' learning outcomes, as evidenced by the increase in the average score and percentage of learning completeness from the first cycle to the second cycle. In addition, students' activities and participation in the learning process also increased. Thus, the group discussion method is effective as one of the collaborative learning approaches in improving student learning outcomes in PAI-BP subjects.